Knowledge and attitude of secondary schools students toward orthodontic treatment in Al amamra district - AbuAisha, Aisha A.; Eshumani, Fatima A.; Alhour , Tahany (Aljameai)
Abstract: One of the most prevalent dental problems affecting oral health is malocclusion. However, people start to see malocclusion in different way specially for esthetic appearance. Hence, orthodontic treatment becomes prevalent and necessary. The goal of this study was to know the range of knowledge and attitude of secondary school students toward orthodontic treatment in Al amamra district in Libya. A descriptive cross sectional study involved 203 students. The questionnaire method was used to collect data and the collected data was analyzed using the SPSS ( version 16). the study revealed high difference of knowledge and attitude score between males and females ,which showed more scores in case of males. For Recommendation we advise to keep wear preservative appliance to maintenance teeth alignment after complete the treatment. As well as, we suggested starting orthodontic treatment in early ages to improve aesthetic appearance المستخلص: إن سوء الإطباق هو أحد أكثر مشاكل الأسنان شيوعًا التي تؤثر على صحة الفم. ومع ذلك، يبدأ الناس في رؤية سوء الإطباق بطريقة مختلفة خاصة فيما يتعلق بالمظهر الجمالي. وبالتالي، أصبح العلاج التقويمي شائعًا وضروريًا. كان الهدف من هذه الدراسة هو معرفة مدى المعرفة والسلوك لدى طلاب المدارس الثانوية تجاه العلاج التقويمي في مدينة العمامرة في ليبيا. شملت الدراسة المقطعية الوصفية 203 طالبًا. تم استخدام طريقة الاستبيان لجمع البيانات وتم تحليل البيانات التي تم جمعها باستخدام برنامج SPSS (الإصدار 16). كشفت الدراسة عن وجود اختلاف كبير في درجة المعرفة والسلوك بين الذكور والإناث، والتي أظهرت تفوق الذكور. للتوصية، ننصح بالاستمرار في ارتداء جهاز وقائي للحفاظ على الإصطفاف السليم للأسنان بعد الانتهاء من العلاج. وكذلك اقترحنا البدء في العلاج التقويمي في سن مبكرة لتحسين المظهر الجمالي.